A limit reference point to prevent recruitment overfishing of Pacific bluefin tuna. (April 2017) - Nakatsuka, Shuya; Ishida, Yukimasa; Fukuda, Hiromu; Akita, Tetsuya
Abstract: Pacific bluefin tuna (PBF) ( Thunnus orientalis ) is commercially important in the North Pacific Ocean. Although its stock has been relatively low for decades, international discussions on a long-term management framework, including the definition of a limit reference point (LRP), have only recently started. This paper argues that an LRP for PBF could be developed by determining a biomass level that would prevent recruitment overfishing. First, it reviews the development of LRPs for various tuna species and demonstrates that most of these limits are not necessarily based on biological information on the respective species. Then, the current management of PBF is also reviewed as background information for considering an LRP for PBF. Finally, a variety of simple analyses of the stock–recruitment relationship of PBF are conducted to find a biomass level that would prevent recruitment overfishing—i.e. an LRP below which stocks should not fall. It is concluded that, for the first time to our knowledge, defining such an LRP for a tuna species is possible (about 30 thousand tonnes or 5% of estimated unfished spawning stock biomass in our calculation). Not only is the LRP based on actual experience, but also the logic behind it would be easier for stakeholders to understand than the theoretical LRPs used elsewhere. This LRP should be useful in future in more comprehensive management framework, such as one through management strategy evaluations, in which stakeholder involvement in decision-making is crucial. Highlights: An empirical limit reference point (LRP) for Pacific bluefin tuna is proposed. It is defined as a point above which good recruitment is expected. It is calculated by analyzing the species' stock–recruitment relationship. Data supports that the stock can be managed sustainably using such an LRP. Its easy-to-understand nature should promote stakeholder buy-in.